Custo-utilidade da mamoplastia redutora pelo Sistema Único de Saúde - Araújo, Carlos Delano Mundim [UNIFESP] (2010)
Introduction: Economic evaluation is important for decision making regarding resource allocation. There are few cost-utility or cost-effectiveness and breast hypertrophy studies. Objective: to determine the cost-utility ratio in reduction mammaplasty in Brazilian national health care system (Sistema Único de Saúde). Methods: controlled, interventional, prospective, analytical, primary study with randomization in human beings. From July 2008 to February 2009, in the Hospital das Clínicas Samuel Libânio (HSCL) (Plastic Surgery ambulatory) of the Vale do Sapucaí (UNIVÁS) University, were selected 60 patients with breast hypertrophy. The groups were randomly divided into control group: 30 patients followed for six months and study group: 30 patients undergoing reduction mammaplasty. Direct costs were obtained from medical records. The utility was evaluated through the Short Form Health Survey Instrument 6D (SF-6D). Results: After six months of evaluation, the study group showed improvements in utility at an average cost of direct Rdollar 391.47. Conclusion: reduction mammaplasty in the Brazilian national health care system provides cost-utility ratio equivalent to Rdollar 536,26/1QALY.